Sex‐based trade‐offs in the innate and acquired immune systems of Sternotherus minor. Issue 10 (19th October 2020) - López‐Pérez, Jorge E.; Meylan, Peter A.; Goessling, Jeffrey M.
Abstract: Longevity patterns in most vertebrates suggest that females benefit most from maintenance investment. A reversed longevity pattern in loggerhead musk turtles ( Sternotherus minor ) allowed us to test trade‐offs between maintenance and survivorship. We tested the hypothesis that the sex with greater longevity has greater maintenance than the sex with shorter longevity. We also compared the following parameters between sexes: Bactericidal ability (BA) and heterophil:lymphocyte ratios (HLR). Baseline blood samples were collected from turtles in the field; a subset of turtles was returned to a laboratory for experiments of acquired immune responses to sheep red blood cells (SRBC). We found no support for the original hypothesis of reversal in sex‐dependent immune trade‐offs (difference between sex SRBC titers: p  = .102; interaction between treatment and sex: p  = .177; difference between treatments: p  < .001; effect of sex on BA: p  = .830; effect of sex on HLR: p  = .717). However, we did find support for sex‐dependent differences in immunity in the relationship between HLR and body condition (BCI) (effect of BCI on HLR: p  = .015). In field conditions, we found that males with higher body condition indices express stressed phenotypes more than males with lower body condition indices ( p  = .002). However, females expressed similar stress loads across all body conditions ( p  = .900). Testosterone concentrations were assayed in free‐living turtles and were not related to any of the immune parameters. Our results suggest that the immune systems play an important role in balancing sex‐specific responses to different selective pressures in S. minor . Abstract : We tested how loggerhead musk turtle ( Sternotherus minor ) acquired immune responses vary between sexes and found no significant effect of sex on the increase in sheep red blood cell (SRBC) titer in response to SRBC immunization when compared to a saline negative control. Markers indicate means and bars indicate 95% confidence intervals Research Highlights: In male Sternotherus minor, heterophil:lymphocyte ratios (HLR) were positively correlated to body condition index (BCI); females expressed equal HLR across BCI. Male and female turtles had similar innate and acquired immunity.